Competences necessary for a social entrepreneur: a case study of Latvia - Sannikova, Aija; Vevere, Velga; Titko, Jelena (Business: Theory and Practice, 2023)
Social entrepreneurship as a specific kind of business has been developing in Latvia since 2018, and it is a little researched field. Achieving the goals of social entrepreneurship is facilitated by several factors, including the competences of the social entrepreneur him/herself. The present research aims to identify the general basic knowledge, skills and competences necessary for a social entrepreneur in Latvia. The authors made a review of theoretical literature on the role of managerial competencies in social enterprises and analysed the results of surveys of social entrepreneurs and their institutional partners – university teaching personnel – conducted in Latvia. The research found that there were areas of general knowledge, skills and competences of social entrepreneurs that were rated as equally important by both groups surveyed, yet the social entrepreneurs gave more importance to competences related to business goals and opportunities. The present research makes a scientific contribution in two aspects: 1) the identified general competencies required for a social entrepreneur could serve as a basis for further research to measure the actual competencies of social entrepreneurs; 2) the research contributes to an institutional framework for the social entrepreneurship ecosystem by developing recommendations for cooperation partners – those involved in adult lifelong learning, incl. universities, for the development of competencies in social entrepreneurs.